2012
DOI: 10.1007/s13105-012-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal zinc intake of Wistar rats has a protective effect in the alloxan-induced diabetic offspring

Abstract: Zinc has a role in the synthesis, storage, and secretion of insulin, and has been suggested to be beneficial when used in the diabetic state. Effect of zinc intake in pregnant rats has been studied here on diabetized offspring. Pregnant rats were divided in two groups; the control group received normal food and water, and the experimental group received zinc sulfate during pregnancy and 3 weeks after offspring birth. Male offspring from the control (C) and experimental (E) groups were divided each in three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Rodent studies reported that zinc supplementation during pregnancy can protect the offspring against experimentally induced T1D . Zinc supplementation in the rodent model studies appeared to be supra‐physiological.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Rodent studies reported that zinc supplementation during pregnancy can protect the offspring against experimentally induced T1D . Zinc supplementation in the rodent model studies appeared to be supra‐physiological.…”
Section: Discussionmentioning
confidence: 93%
“…Oxidative stress is involved in the destruction of pancreatic β‐cells and the antioxidant properties of zinc may protect against T1D . Both population‐based and rodent studies report that zinc supplementation decreases the risk of T1D . A population‐based study reports, that zinc has an U‐shaped effect on the risk of T1D .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akita mice become diabetic spontaneously at the age of 3–4 weeks and show robust hyperglycemia by 12 weeks (27). Therefore, it is a better than the induced diabetes models such as NOD-autoimmune depletion of beta cells (8), OVE 26-the non-specific gene expression of beta cells (9), and Streptozotocin- or Alloxan-chemicals destruction of beta cells (1012). These mice develop cardiac fibrosis, endothelium-myocyte uncoupling (5;13), impaired contractility of cardiomyocytes and cardiac dysfunction (4;14).…”
Section: Introductionmentioning
confidence: 99%
“…For example, zinc itself may benefit the overall development of the pregnant rats and fetus as nutrition, resulting in the observed fetal development improvement. Maternal zinc intake has other benefits, such as protecting alloxan‐induced diabetic offspring and nickel‐induced hepatotoxicity . Furthermore, rats co‐administered with zinc displayed reduced mercury levels in the placenta, suggesting that the decreased mercury‐induced toxicity in fetuses might also be attributed to the ability of zinc to decrease the absorption of mercury into the maternal body.…”
Section: Discussionmentioning
confidence: 99%